STRATEGI ADVOKASI MELALUI PROSES NONLITIGASI DALAM RANGKA PEMBAHARUAN PROSES PERADILAN DI INDONESIA: STRATEGI ADVOKASI MELALUI PROSES NONLITIGASI DALAM RANGKA PEMBAHARUAN PROSES PERADILAN DI INDONESIA - Wahyu subakti; Syed Agung Afandi; Reski Lestari (LPPM Universitas Abdurrab, 2023)
This study aims to explain the advocacy strategy through the non-litigation process in the context of reforming the judicial process in Indonesia. Mediation in court is an institution and empowerment of peace (court connected mediation) with a philosophical foundation that is Pancasila which is the basis of the Indonesian state, especially the fourth precept